Selling the Cochlear Implant - Fiona A. Kumari Campbell (Disability Studies Quarterly, 2005)
This article explores the power of rhetoric and representation, of marked bodies known to the hearing world as "the Deaf," and also an artifact branded as a cochlear implant (hereafter referred to as CI). The CI invokes a story of culture wars ostensibly about ontological disputation. The case study examines the conditions of the implant's production, the kinds of commitments invoked in product development and the processes of bandwagoning that led to the creation of a cochlear implant black box. Argument concludes that the normalization of the cochlear implant is due not just to the obtainment of inter-organizational networks of "relevant" social groups but was made possible through a deferment to negative ontologies of Deafness and the deployment of the inherent preferability of "hearing" as social capital. The study concludes that technologies of cochlear implantation, by being promoted as a technology of "treatability" in effect produce agreements and foreclose discussion on the contestability of the concepts of deafness, hearingness, aberrancy and normalcy.
Keywords: ontology; cochlear implants; Deaf culture; rhetoric; Disability Studies; deafness; hearing; science ethics.